Quality of Life in Children with Epilepsy: A Bibliometric Analysis. - Kılıç, Kızbes Meral; Aydın, Hilal (Archives of Epilepsy, 2025)
Objective: The aim of this study was to explore research related to the quality of life (QOL) of children with epilepsy using bibliometric analysis. Methods: This study used the Web of Science Core Collection database. Articles in this widely used globally database were searched on February 14, 2024, using the following keywords: ("epilepsy" or "seizure" or "convulsion" or "epileptic" or "status epilepticus") and ["quality of life" or "QOL" or "life quality" or "health related quality of life (HRQOL)" or "health-related quality of life" or "HRQOL"] and ("children" or "child" or "childhood" or "infant" or "adolescent"). Results: This study, conducted in 1991, on the QOL of children with epilepsy, revealed that 1,810 articles in English had been published in this domain. Examination of citations of research in this field revealed that the most cited article was "Definition of drug resistant epilepsy: consensus proposal by the ad hoc Task Force of the International League Against Epilepsy Commission on Therapeutic Strategies". Examination of inter-country collaborations in studies on the subject revealed that the United Kingdom and the United States of America (USA) engaged in the most collaborations. Specifically, the United Kingdom collaborated most with the USA (n=69), followed by Italy (n=31), France (n=30), Germany (n=29), and the Netherlands (n=28). Conclusion: Our scan of the literature revealed no previous bibliometric studies in which the subject of QOL in pediatric epilepsy patients was addressed. This bibliometric study analyzed sources, authors, researchers, institutions, links, countries, keywords, topics, and themes, investigating epileptic children's QOL.